Al and Si Influences on Hydrogen Embrittlement of Carbide-Free Bainitic Steel - Yanguo Li; Cheng Chen; Fucheng Zhang (Advances in Materials Science and Engineering)
A first-principle method based on the density functional theory was applied to investigate the Al and Si influences on the hydrogen embrittlement of carbide-free bainitic steel. The hydrogen preference site, binding energy, diffusion behaviour, and electronic structure were calculated. The results showed that hydrogen preferred to be at the tetrahedral site. The binding energy of the cell with Si was the highest and it was decreased to be the worst by adding hydrogen. The diffusion barrier of hydrogen in the cell containing Al was the highest, so it was difficult for hydrogen to diffuse. Thus, hydrogen embrittlement can be reduced by Al rather than Si.